Synthesis and Characterization of Mn(II), Fe(III), Co(II) and Ni(II) Complexes of Anthracene Carboxaldehyde Semicarbazone - Marykutti, P.V.; Parameswaran, Geetha (Asian Journal of Chemistry, 2010)
Complexes of Mn(II), Fe(III), Co(II) and Ni(II) with Schiff base formed by condensation of semicarbazide hydrochloride and anthracene carboxaldehyde have been synthesized and their physico- chemical properties have been investigated by elemental analysis, magnetic measuremens, molar conductance, electronic, spectroscopy, Infra-red spectroscopy and thermal studies. The ligand was found to be bidentate chelating agent for the metal ions. Thermal decomposition data of Co(II), Ni(II) and Mn(II) have been analysed to obtain the activation energy, entropy of activation and frequency factor based on Coats-Redfern equation. The relative thermal stability of the chelates can be given as [CoL2(H2O )2] ≈ [NiL2(H2O )] > [MnL2(H2O )2]..